2020
DOI: 10.1161/circresaha.120.316365
|View full text |Cite
|
Sign up to set email alerts
|

How Will Genetics Inform the Clinical Care of Atrial Fibrillation?

Abstract: Susceptibility to atrial fibrillation (AF) is determined by well-recognized risk factors such as diabetes mellitus or hypertension, emerging risk factors such as sleep apnea or inflammation, and increasingly well-defined genetic variants. As discussed in detail in a companion article in this series, studies in families and in large populations have identified multiple genetic loci, specific genes, and specific variants increasing susceptibility to AF. Since it is becoming increasingly inexpensive to obtain gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 139 publications
0
16
0
Order By: Relevance
“…We previously proposed that it should be patients diagnosed before 45 years of age. However, our results demonstrate that the likelihood of a disease-associated variant is approximately the same (10%) in the 40- to 49- and 50- to 59-year age groups, with a decrease after 60 years of age. These data suggest that genetic testing for early-onset AF could be considered in patients diagnosed with AF up to 60 years of age, with a stronger recommendation for patients diagnosed before 30 years of age.…”
Section: Discussionmentioning
confidence: 87%
“…We previously proposed that it should be patients diagnosed before 45 years of age. However, our results demonstrate that the likelihood of a disease-associated variant is approximately the same (10%) in the 40- to 49- and 50- to 59-year age groups, with a decrease after 60 years of age. These data suggest that genetic testing for early-onset AF could be considered in patients diagnosed with AF up to 60 years of age, with a stronger recommendation for patients diagnosed before 30 years of age.…”
Section: Discussionmentioning
confidence: 87%
“…Relatively inexpensive domestic infusion monitoring devices have been marketed, but they can only be monitored individually and cannot be networked for systematic management [ 1 ]. Clinical infusion work still suffers from untimely fluid replacement, inaccurate infusion speed, and failure to detect infusion failure in time.…”
Section: Introductionmentioning
confidence: 99%
“…Similar to this study, multiple studies have observed the trend of significant association of AF recurrence only with a higher PRS and generally not with the SNVs themselves. One likely reason for this is that the SNVs associated with AF are frequently located outside of coding regions and thus not directly involved in the pathogenesis of AF [41,42]. Indeed, all eight SNVs investigated here are located in non-coding regions.…”
Section: Discussion Of Resultsmentioning
confidence: 91%
“…As such, recent studies have utilized whole-genome sequencing in conjunction with GWAS to permit the calculation of PRS using a far greater number of SNVs [37][38][39][40][44][45][46][47][48]. This has been made possible by the increasing availability of whole-genome sequencing [37,41,42,49].…”
Section: Discussion Of Resultsmentioning
confidence: 99%